Nutrient extraction and exportation by castor bean hybrid lyra - do Nascimento, Martha Santana [UNESP]; Costa Crusciol, Carlos Alexandre [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Zanotto, Maurício Dutra [UNESP] (Sociedade Brasileira de Ciência do Solo, 2012)
Information about nutrient extraction and exportation by crops, as well as the periods of highest nutrient demand is important for an adequate fertilization management. However, there are no studies on the nutrient uptake of short-stature hybrid castor bean. Therefore, the purpose of this study was to evaluate nutrient extraction and exportation by short-stature castor bean hybrid Lyra, in the spring-summer and fall-winter growing seasons. The experiments were conducted in the 2005/2006 spring-summer and 2006 fall-winter growing seasons on an Oxisol, in Botucatu, SP, in a randomized block design, with four replications. The plots consisted of plant samplings, which occurred 17, 31, 45, 59, 73, 97 and 120 days after emergence (DAE) in the spring-summer and 17, 31, 45, 59, 80, 100 and 120 DAB in fall-winter growing season. The growth of hybrid Lyra was slow and nutrient uptake lowest between emergence and the beginning of flowering. The period of highest dry matter (DM) accumulation rates and highest nutrient demand were observed 40 to 80 DAE, in both growing seasons. The order of nutrient extraction by the plants in the spring-summer growing season was: N>K>Ca>Mg>S>P>Fe>Mn>Zn>B>Cu>Mo. In fall-winter, S was more absorbed than Mg. Seed yield was higher in the spring-summer (2.995 kg ha(-1)), but nutrient extraction and exportation per ton of seed were similar in both growing seasons. Around 58 % of N and 84 % of P, and approximately half of the S and B absorbed throughout the cycle were exported with the seeds. However, most of the other nutrients accumulated in the plants returned to the soil in plant residues.
Extração e exportação de nutrientes pelo híbrido de mamona lyra
Keywords: Ricinus communis; uptake curves; uptake rates; seed yield